Menggali Akar Rasisme: Analisis Terhadap Pembentukan Stigma dan Dampaknya Pada Masyarakat - Azmarni Zulfa; Putri Ayu Lestari; Prespi Julihasti; Adinda Desma Andini; Zulfadha Khairunnisa; Rahmi Amanda; Irmayanti Arfah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research delves into the formation of racial stigma and its impact on society, exploring the factors contributing to the emergence of discriminatory attitudes. Utilizing a qualitative descriptive method with a literature review approach, the study investigates historical, cultural, and institutional elements shaping racial perceptions. The analysis not only scrutinizes